CRIMINILOGICAL REVIEW OF RECIDIVISTS IN THEFT CRIMES AT CLASS IIB TASIKMALAYA PENITENTIARY - Hisyam, Sultan Alif; Rahayu, Mulyani (Universitas Nusa Cendana, 2025)
This article discusses the implementation of Article 14, Paragraph 1, Letter (C) of Law Number 12 of 1995 concerning corrections in efforts to prevent recidivism of theft cases in Buleleng Regency. This research is essential for understanding the effectiveness of correctional policies in reducing recidivism rates, particularly among theft offenders. Using a qualitative approach, this study identifies the factors influencing the success of rehabilitation programs carried out in correctional institutions. The findings indicate that comprehensive rehabilitation strategies, including education and vocational skills, significantly impact the social reintegration of inmates after completing their sentences. The study also outlines the challenges in implementing this law, which include a lack of community support and limited available resources. This study recommends strengthening cooperation between correctional institutions and the community, as well as the importance of tighter supervision of released inmates to prevent them from re-engaging in criminal activities. Keywords: Recidivism; Corrections; Prevention